Kandungan Protein Roti Tawar Dengan Subtitusi Tepung Ikan Gabus (Channa Striata) - Adriyani Adam; Firdaus Syafii; Saiful Saiful (Poltekkes Kemenkes Mataram, 2020)
Background : Malnutrition problem is still the top priority in Indonesia and one of focuses in the Medium Term Development Plan (RPJMN) for 2020-2024. Riskesdas 2018, show the percentage of nutritional status of stunting under five age in Indonesia 2018 was 25.7%, in West Sulawesi Province was the second highest contributor for stunting children in Indonesia with prevalence 41.8%. One of the preventive efforts that can be done is through the development of food products. In this study, the development of white bread with the substitution of Channa Striata fish flour was expected to enrich the nutritional content of bread, especially protein. In this study, using Channa Striata fish because it has a higher protein content than other foodstuffs known as sources of protein such as eggs, chicken and beef. Apart from protein, Channa Striata fish also has a high albumin content which can be used in wound healing. This aims of this study to determine the protein content of white bread with the substitution of Channa Striata fish meal by 5% and 10% Methods : This type of research is an experimental study to determine the protein content in white bread with the substitution of Channa Striata fish meal by 5% and 10%. The analytical method used to assess protein content is the kjeidhal method, which is a simple method for determining total nitrogen in amino acids, proteins, and nitrogen-containing compounds. The test was carried out at Health Laboratory South Sulawesi. Results : The results showed that the protein content of white bread with a substitution of 5% was 9.03 grams, and a substitution of 10% was 10.38 grams. Conclusion : The conclusion of this study was even more substitution of Channa Striata fish flour used, will increase protein content in the white bread.